2017
DOI: 10.1111/pde.13244
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Elimination Diets in Atopic Dermatitis—A Comprehensive Review

Abstract: A comprehensive literature review reveals some promising results and several areas in need of further study. More evidence is needed to form a strong foundation for recommendations regarding the utility and role of elimination diets in AD management, but current evidence suggests that strict diet management is not effective in the treatment AD in the vast majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Despite some conflicting results [48, 49], case-controlled studies of AD sufferers have shown higher blood levels of linoleic acid (precursor of n-6 PUFA) and lower levels of n-3 PUFA [50, 51]. However, from studies in literature concerning the effects of diet on AD [5256] emerges that a strict diet management is not effective in general in the treatment of AD [57]. Further studies are therefore needed in this regard [9].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Despite some conflicting results [48, 49], case-controlled studies of AD sufferers have shown higher blood levels of linoleic acid (precursor of n-6 PUFA) and lower levels of n-3 PUFA [50, 51]. However, from studies in literature concerning the effects of diet on AD [5256] emerges that a strict diet management is not effective in general in the treatment of AD [57]. Further studies are therefore needed in this regard [9].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…One possibility is that those who deviate from popular opinion are more skeptical and thus likely to devote more time to seeking reputable sources. Additionally, much of the literature is not as definitive as online bloggers make it seem when linking food to skin conditions [15,16]. Therefore, it is not surprising why many who use reputable sources would be more in disagreement that nutrition affects skin health.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consistent evidence to recommend food avoidance or dietary supplements to reduce or prevent AD symptoms. While there is low-level evidence for specific food avoidance leading to AD improvement in patients with identified food allergies, 14,15 there is no evidence to support empiric food avoidance in all pediatric AD patients. 14,15 There is limited evidence to support vitamin D or symbiotic supplementation.…”
Section: Diet and Oral Supplementsmentioning
confidence: 99%